THE INFLUENCE OF ADOLESCENTS’ TEMPERAMENTAL CHARACTERISTIC ON THE LEVEL OF RELIGIOUSITY: A CASE STUDY OF STUDENTS AT DARUSSALAM GONTOR UNIVERSITY PONOROGO: - Gunawardana, Savier Nayaka; Puspitasari, Niken Sylvia; Alfadla, Maya Tsuroya; Zaki, Rifqi Baihaqi; Sasongko, Muhammad Rafi Dhiaulhaq (Jurnal Penelitian Ilmiah INTAJ, 2025)
The pesantren-based university has regulations aimed not only at enhancing the academic aspects but also at improving the religiosity of its students. However, some regulations make pesantren students feel burdened, which eventually leads to temperamental characteristics that hinder the students' development of their religiosity. This creates a dilemma where the pesantren's main goal is to strengthen the religiosity of its students. The purpose of this study is to determine the influence of temperamental characteristics on the level of religiosity among pesantren students. This research uses a quantitative method with a correlational design. Data collection was carried out using random sampling by distributing questionnaires to undergraduate students at Darussalam Gontor University, with a total of 100 respondents. The data obtained were analyzed using simple linear regression. The results of the study show that temperamental characteristics have only a 6% influence on religiosity, while 94% of religiosity is influenced by other factors outside the scope of this study. This proves that temperamental characteristics do not significantly affect the level of religiosity among pesantren students.